Exploration of the Pharmacokinetic-Pharmacodynamic Relationships for Fosfomycin Efficacy Using an In Vitro Infection Model - VanScoy, Brian D. (Antimicrob Agents Chemother, 2015)
Fosfomycin, a phosphonic class antibiotic with a broad spectrum of antibacterial activity, has been used outside the United States since the early 1970s for the treatment of a variety of infections. In the United States, an oral (tromethamine salt) formulation is used for uncomplicated urinary tract infections. Recently, there has been interest in the use of an intravenous solution (ZTI-01) for the treatment of a broad range of infections associated with multidrug-resistant bacteria. In this era of multidrug-resistant bacteria with few treatment options, it is critical to understand the pharmacokinetic-pharmacodynamic (PK-PD) determinants for fosfomycin efficacy. Since such data are limited, a one-compartment in vitro infection model was used to determine the PK-PD index associated with efficacy and the magnitude of this measure necessary for various levels of effect. One challenge isolate (Escherichia coli ATCC 25922, for which the fosfomycin agar MIC is 0.5 mg/liter and the broth microdilution MIC is 1 mg/liter) was evaluated in the dose fractionation studies, and two additional clinical E. coli isolates were evaluated in the dose-ranging studies. Mutation frequency studies indicated the presence of an inherently fosfomycin resistant E. coli subpopulation (agar MIC = 32 to 64 mg/liter) within the standard starting inoculum of a susceptibility test. Due to the presence of this resistant subpopulation, we identified the percentage of the dosing interval that drug concentrations were above the inherent resistance inhibitory concentration found at baseline to be the PK-PD index associated with efficacy (r(2) = 0.777). The magnitudes of this PK-PD index associated with net bacterial stasis and 1- and 2-log(10) CFU/ml reductions from baseline at 24 h were 11.9, 20.9, and 32.8, respectively. These data provide useful information for modernizing and optimizing ZTI-01 dosing regimens for further study.